Where Are You? The Effect of Uncertainty and Its Visual Representation on Location Judgments in GPS-Like Displays. - Hegarty, Mary; Friedman, Alinda; Boone, Alexander P.; Barrett, Trevor J. (Journal of Experimental Psychology. Applied, 2016)
Two experiments revealed how nonexperts interpret visualizations of positional uncertainty on GPS-like displays and how the visual representation of uncertainty affects their judgments. Participants were shown maps with representations of their current location; locational uncertainty was visualized as either a circle (confidence interval) or a faded glyph (indicating the probability density function directly). When shown a single circle or faded glyph, participants assumed they were located at the center of the uncertain region. In a task that required combining 2 uncertain estimates of their location, the most common strategy--integration--was to take both estimates into account, with more weight given to the more certain estimate. Participants' strategies were not affected by how uncertainty was visualized, but visualization affected the consistency of responses, both within individuals and in relation to models of individual's preferred strategies. The results indicate that nonexperts have an intuitive understanding of uncertainty. Rather than arguing for a particular method of visualizing uncertainty, the data suggest that the best visualization method is task dependent.